Pemberdayaan Kelompok Istri Nelayan Melalui Keterampilan Manajemen Pakan Lengkap Dalam Meningkatkan Produktivas Domba - Rosmaiti Rosmaiti; F.Hafiz Saragih; Kiagus Muhammad Zain Basriwijaya (Asosiasi Dosen Akuntansi Indonesia, 2021)
The coronavirus outbreak or Covid-19 has become a global pandemic and has had a tremendous impact on the economy of the community, one of which is on sheep/goat breeders in Gampong Kuala Idi Cut, East Aceh Regency. This makes it difficult for breeders to herd their livestock, look for animal feed, make buying and selling transactions. Therefore, breeders who are members of the fishermen's wife group are given the training to add skills in complete feed management. The evaluation will be carried out through posttests and questions and answer to find out if there are changes in the knowledge of feed processing technology by utilizing existing agricultural waste. After the farmer gets empowerment regarding the kinds of feed processing technology. Farmers are aware of the potential feed source that comes from agricultural waste. Breeders have begun to regulate balanced feeding derived from forage in the form of grass combined with legumes and agricultural waste such as rice straw in a balanced manner and according to the sheep's nutritional needs. There is an inhibiting factor, namely the lack of capital for breeders who are less able to meet their feed needs because they still have to buy them and compete with other livestock.